Donor Smoking Is Associated With Pulmonary Edema, Inflammation and Epithelial Dysfunction in Ex Vivo Human Donor Lungs. Issue 10 (21st August 2014) - Ware, L. B.; Lee, J. W.; Wickersham, N.; Nguyen, J.; Matthay, M. A.; Calfee, C. S.; the California Transplant Donor Network
<x xml:space="preserve">Abstract</x> Although recipients of donor lungs from smokers have worse clinical outcomes, the underlying mechanisms are unknown. We tested the association between donor smoking and the degree of pulmonary edema (as estimated by lung weight), the rate of alveolar fluid clearance (AFC; measured by airspace instillation of 5% albumin) and biomarkers of lung epithelial injury and inflammation (bronchoalveolar lavage [BAL] surfactant protein‐D (SP‐D) and IL‐8) in ex vivo lungs recovered from 298 organ donors. The extent of pulmonary edema was higher in current smokers (n = 127) compared to nonsmokers (median 408 g, interquartile range [IQR] 364–500 vs. 385 g, IQR 340–460, p = 0.009). Oxygenation at study enrollment was worse in current smokers versus nonsmokers (median PaO2/FiO2 214 mm Hg, IQR 126–323 vs. 266 mm Hg, IQR 154–370, p = 0.02). Current smokers with the highest exposure (≥20 pack years) had significantly lower rates of AFC, suggesting that the effects of cigarette smoke on alveolar epithelial fluid transport function may be dose related. BAL IL‐8 was significantly higher in smokers while SP‐D was lower. These findings indicate that chronic exposure to cigarette smoke has important effects on inflammation, gas exchange, lung epithelial function and lung fluid balance in the organ donor that could influence lung function in the lung transplant recipient.